The Wa Concept and its Effects on Deaf Education in Japan - Dushanta, Alyarizki (East Asian Review, 2024)
Japanese society has been noted for the emphasis it places on social harmony. As with other cultural values, ideas of harmony may have played a part in written and unwritten rules of the community. As a marginalized group whose existence itself is seen to not be in accordance with the norm, disabled people might particularly be affected by such normative values. This research discusses how values within the wa concept are interwoven in the educational practice for deaf children, as well as the effects it has on them. Values of self-reliance and ‘sameness’ pushes deaf children into assimilation, and to become independent society members that can adapt to the comfort of their surroundings. The deaf education system that has been permeated by the wa concept has resulted in numerous issues, mainly in regards to the childrens’ linguistic skills, as well as social and emotional development. This research shows that while the wa concept is supposed to create societal harmony, normative values created through the lens of the wider and typical society could create a paradoxical situation when applied to marginalized groups such as deaf people.